ETD Vol. 15, n. 1 (2013) - Costa Junior, Maurício Pereira da (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2014)
ETD Vol. 15, n. 1 (2013)Link de acesso ao númerohttp://www.fae.unicamp.br/revista/index.php/etd/issue/view/271/showToc